Makna Proses Kebijakan: Menyingkap Kontroversi Pembangunan Bali Nirwana Resort - Santoso, Purwo; Saskarayasa, I Ketut Adhi (Jurnal Ilmu Sosial dan Ilmu Politik, 2002)
Mainstream public policy theory has been heavily biased toward administrative approach which tends to oversimplify policymaking as internal process within state-bureaucracy. Policy process is perceived as nothing more than the exercise of authority even when legitimacy of his or her decision is undetected. In their attempt to assess the appropriateness of those theoretical presumption, the authors scrutinize the controversy within the process of developing a tourist resort: Bali Nirwana Resort. In line with the trend in renewal the studi of public administration, the authors suggest a more political, consensus-based theory of policy-process.